2017
DOI: 10.1021/acs.orglett.6b03634
|View full text |Cite
|
Sign up to set email alerts
|

A Synthesis of “Dual Warhead” β-Aryl Ethenesulfonyl Fluorides and One-Pot Reaction to β-Sultams

Abstract: Herein, we report an operationally simple, ligand- and additive-free oxidative boron-Heck coupling that is compatible with the ethenesulfonyl fluoride functional group. The protocol proceeds at room temperature with chemoselectivity and E-isomer selectivity and offers facile access to a wide range of β-aryl/heteroaryl ethenesulfonyl fluorides from commercial boronic acids. Furthermore, we demonstrate a "one-pot click" reaction to directly transform the products to aryl-substituted β-sultams.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(38 citation statements)
references
References 39 publications
0
38
0
Order By: Relevance
“…Despite this, there are very few references in the literature which highlight the SF group as synthetic intermediates. Currently, our work is aimed at fully investigating the synthetic potential of the SF group [14,15]. Crystal structure analysis of title compound revealed that the cyclopentane moiety of the molecule is distorted as the carbon atom C5 is tipped up towards the direction of methylcarboxylate moiety.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, there are very few references in the literature which highlight the SF group as synthetic intermediates. Currently, our work is aimed at fully investigating the synthetic potential of the SF group [14,15]. Crystal structure analysis of title compound revealed that the cyclopentane moiety of the molecule is distorted as the carbon atom C5 is tipped up towards the direction of methylcarboxylate moiety.…”
Section: Discussionmentioning
confidence: 99%
“…In 2017, Arvidsson and co-workers reported an operationally simple method for ligand-and additive-free oxidative Heck couplings of aryl boronic acids (57) with ESF (51) (Scheme 10) [65]. The reactions proceeded at room temperature with good chemoselectivity and E-selectivity and offered facile access to a wide range of β-aryl/heteroaryl ethenesulfonyl fluorides (58) from the commercially available boronic acids (57).…”
Section: Fluorine-containing Vinyl Sulfur Compounds As the Cross-coupmentioning
confidence: 99%
“…Furthermore, the oxidative Heck cross-coupling reactions have become attractive for modern organic synthesis due to advantages such as efficiency, mild reaction conditions, good functional group tolerance, and widespread applications [62][63][64]. In 2017, Arvidsson and co-workers reported an operationally simple method for ligand-and additive-free oxidative Heck couplings of aryl boronic acids (57) with ESF (51) (Scheme 10) [65]. The reactions proceeded at room temperature with good chemoselectivity and E-selectivity and offered facile access to a wide range of β-aryl/heteroaryl ethenesulfonyl fluorides (58) from the commercially available boronic acids (57).…”
Section: Fluorine-containing Vinyl Sulfur Compounds As the Cross-coupmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1b(2)]. [14] In pursuit of a more general Heck-type coupling process with ESF, [15], [16] we turned to organic iodides. Although the preliminary attempts using phosphine ligand or base failed (see SI), the combination of aryl halide/silver(I) salt [17] was found the fix for this palladium catalyzed coupling process between iodobenzene (2a) and ESF (1) (equation 1).…”
Section: Hhs Public Accessmentioning
confidence: 99%